The role of exoticism in international contemporary art in the era of globalization – an empirical study of international art magazines from 1971 to 2010 - Yun, Kusuk (Revista do Instituto de Estudos Brasileiros, 2018)
In the era of globalization, the visibility of non-Western artists has become more and more important. In trying to enhance global diversity and cultural relativism, an exotic cultural form has emerged. As a result, peripheral artists can be tempted to represent their own cultural identity as a new esthetic value, but through a stereotyped image suited to Western tastes. Through the study of articles about Japanese, Chinese, and Korean artists published in international art magazines, we will look at the growth in their visibility and the development of clichés and stereotypes toward them. We will aim to discover whether a sense of exoticism generated by the mass-media, by broadcasting stereotyped images, plays an important role in determining the visibility of non-Western countries in international contemporary art.